Parasympathetic withdrawal during 30-15 intermittent fitness test correlates with its` maximal running speed in male handball players - Perandini, L. A.; Chimin, P.; Okuno, N. M.; de Lima, J. R. P.; Buchheit, M.; Nakamura, F. Y. (Journal of Exercise Physiology online, 2009)
Parasympathetic withdrawal parameters estimated during continuous graded exercise have been used as aerobic indices. The purposes of this study were to: 1) examine the pattern of parasympathetic withdrawal during an intermittent fitness test (30-15IFT) and, 2) verify the relationship among parasympathetic withdrawal parameters estimated during 30-15IFT, with its' maximal running speed (VIFT). Thirteen male handball players performed the 30-15IFT. Heart rate variability (HRV) indices were estimated every 45 s over the 30-15IFT until 85% of maximal heart rate or 15 km.h-1, and plotted against time to estimation of parasympathetic withdrawal parameters (t, amplitude (A) and area under the curve (AUC)). Parasympathetic withdrawal was well adjusted to a mono-exponential decay curve-fitting (R2 = 0.96-0.97). The parasympathetic withdrawal parameters t and A were poorly correlated with VIFT (r = 0.29-0.46, P > 0.05), whereas AUC was moderate-to strongly correlated with VIFT (r = 0.64-0.80, P < 0.05). Therefore, AUC derived from the mono-exponential decay pattern during 30-15IFT can be considered an aerobic index of intermittent exercise. ABSTRACT FROM AUTHOR